2011
DOI: 10.1161/strokeaha.110.607697
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Nighttime Heart Rate Variability Is Associated With Increased Stroke Risk

Abstract: Background and Purpose-Prediction of stroke in healthy individuals is challenging and there is a diurnal variation of stroke onset. We hypothesized that heart rate variability with a focus on nighttime heart rate variability will predict the risk of stroke in apparently healthy middle-age and elderly subjects. Methods-The population-based cohort of the Copenhagen Holter Study, consisting of 678 healthy subjects between age 55 and 75 years with no history of cardiovascular disease or stroke, was evaluated. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 37 publications
3
75
1
Order By: Relevance
“…Daily variability in stroke occurrence can reflect autonomic nervous system modulations and even more its modifications with aging, which is suspected to facilitate stroke. Vagal tonic modulation during the night, in fact, is higher in young males and decreases with aging and it has been associated with stroke risk [61, 62]. These differences may partially justify the different circadian distribution of stroke onset between males and females and during aging.…”
Section: Discussionmentioning
confidence: 99%
“…Daily variability in stroke occurrence can reflect autonomic nervous system modulations and even more its modifications with aging, which is suspected to facilitate stroke. Vagal tonic modulation during the night, in fact, is higher in young males and decreases with aging and it has been associated with stroke risk [61, 62]. These differences may partially justify the different circadian distribution of stroke onset between males and females and during aging.…”
Section: Discussionmentioning
confidence: 99%
“…13 Though informative, this study was limited by a small sample size, few stroke events, and examination of time-domain HRV measures only. We have expanded on this work by utilizing a large prospective bi-racial cohort, time- and frequency-domain HRV indices, and by evaluating potential effect modification by diabetes status.…”
Section: Discussionmentioning
confidence: 99%
“…12 Another study reported an association between low nighttime HRV and increased risk of incident ischemic stroke, 13 but was limited by small sample size and few stroke events. The clinical value of HRV for identifying people at high risk of stroke is unknown; no studies have evaluated daytime HRV as would be assessed in a routine clinic visit.…”
Section: Introductionmentioning
confidence: 99%
“…Lower heart rate variability (HRV) is an early manifestation of some of the shared risk factors of stroke such as poor physical activity, emotional stress, diabetes, hypertension and end-stage renal disease. However, there is paucity n the literature with regards to HRV and incidence of stroke with one study reporting higher stroke rates in those with lower nighttime HRV [75]. This association may be mediated by several pathways including a higher inflammatory milieu, hypercoagulation and risk of arrhythmias, including AF.…”
Section: Heart Rate Variability and Heart Ratementioning
confidence: 99%